2003
DOI: 10.1080/00015458.2003.11679371
|View full text |Cite
|
Sign up to set email alerts
|

Should Every Patient Undergoing Laparoscopy for Clinical Diagnosis of Appendicitis Have an Appendicectomy ?

Abstract: In cases of clinically suspected acute appendicitis, the rate of negative laparoscopic exploration ranges from 8 to 15%. In that situation, should we remove an apparently normal appendix or should we leave it in place? If there is no evidence of another cause to explain the acute right iliac fossa pain, it seems reasonable to proceed with an appendicectomy even if the appendix looks normal, because the rate of re-operation for recurrent symptoms is up to 6% and an endo-appendicitis which is defined as inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…The experience of the laparoscopic team is very important in this context. We generally agree with the algorithm proposed by (Navez & Therasse, 2003) in the treatment of suspected acute appendicitis. The authors propose to remove a macroscopically normal appendix if one suspects an appendicitis clinically and there are no other findings.…”
Section: Diagnostic and Therapeutic Outcomes Of Laparoscopic Appendecsupporting
confidence: 88%
See 1 more Smart Citation
“…The experience of the laparoscopic team is very important in this context. We generally agree with the algorithm proposed by (Navez & Therasse, 2003) in the treatment of suspected acute appendicitis. The authors propose to remove a macroscopically normal appendix if one suspects an appendicitis clinically and there are no other findings.…”
Section: Diagnostic and Therapeutic Outcomes Of Laparoscopic Appendecsupporting
confidence: 88%
“…It seems that some patients suffer crises of endoappendicitis, that subsides with conservative treatment. Endoappendicitis varies from 11to 26% and the reoperation rate for the patients whose appendix was left in situ is reported to be 6% (Navez and Therasse, 2003). So it might be that the great majority of these patients will not have any problems in the future but for the individual patient the surgeon's decision to leave the appendix behind could mean a readmission, a peritonitis, a second operation, or the persistence of recurrent symptoms.…”
Section: Diagnostic and Therapeutic Outcomes Of Laparoscopic Appendecmentioning
confidence: 99%
“…Navez and Therasse did a retrospective study on whether patients undergoing laproscopic exploration for clinical diagnosis of appendicitis should have an appendicectomy. They concluded that if there is no evidence of another cause to explain the acute right iliac fossa pain, it is sensible to proceed with an appendicectomy even if the appendix looks normal, because the rate of re-exploration for recurrent symptoms is considerable, and endoappendicitis defined as inflammation of the appendicular mucosa is seen [8].…”
Section: Discussionmentioning
confidence: 99%
“…Cases favouring the removal of normal appendix would include those with high clinical suspicion, radiology revealing a faecolith or faecal impaction in the appendix and surgical units where the rate of abscesses is minimal [8]. The presence of 'endoappendicitis' (normal looking serosa but inflammation of inner layers on histology) also justifies this approach [19].…”
Section: Appendicitismentioning
confidence: 99%